The Significations of the Conditional Style in Arabic: An Applied Study in the Commandments of Imam Ali (peace be upon him) - Seyedi, Dr.Seyed Hosein; Mohsen, Dr.Zeina Kdhim; Lahoo, Doaa Rhaif (Thi Qar Arts Journal, 2024)
Reflecting on the review of texts that contain creativity, especially those from the Ahl al-Bayt (peace be upon them), specifically the words of the Prince of Eloquence and the Master of the Eloquent, Imam Ali ibn Abi Talib (peace be upon him), this research attempts to uncover the semantic meanings in the Prince’s (peace be upon him) advice, particularly in the use of conditional sentences. The question arises: Did the conditional style appear in our Imam’s advice in a striking manner to attract the reader’s or listener’s attention? As we know, the conditional style achieves a semantic balance in mentioning the result of the condition, and the result that should be achieved if the initial condition is met. These meanings were frequently used by Imam Ali (peace be upon him) in his advice, as will be indicated throughout the research. This research aims to highlight the conditional phrases frequently used by Imam Ali (peace be upon him) in his numerous pieces of advice that were the subject of study.